Fat metabolism during exercise: a review--part III: effects of nutritional interventions - Jeukendrup, A. E.; Saris, W. H.; Wagenmakers, A. J. (International Journal of Sports Medicine, 1998)
By changes in nutrition it is possible to manipulate fat oxidation. It is often theorized that increasing fat oxidation may reduce glycogen breakdown and thus enhance performance. Therefore, the effects of acute, short-term and long-term fat feeding have been subjects of investigation for many years. Ingestion of long-chain triacylglycerols (LCT) during exercise may reduce the gastric emptying rate and LCT will appear in the plasma only slowly. Medium-chain triacylglycerols (MCT) do not have these disadvantages and they are rapidly oxidized. However, the contribution of MCT to energy expenditure is only small because they can only be ingested in small amounts without causing gastrointestinal distress. So at present, fat supplementation in the hours preceding to or during exercise (either long chain or medium chain triacylglycerols) cannot be recommended. High-fat diets and fasting have been suggested to increase fatty acid availability and spare muscle glycogen resulting in improved performance. Both fasting and short term high-fat diets will decrease muscle glycogen content and reduce fatigue resistance. Chronic high-fat diets may provoke adaptive responses preventing the decremental effects on exercise performance. However, at present, there is little evidence to support this hypothesis. Also from a health perspective, caution should be exercised when recommending high-fat diets to athletes.